Distribution of Airborne Lead in Metro Manila, Philippines (2008)
The adverse effects of heavy metal contamination, such as lead in the environment, have been a worldwide concern. In the Philippines, the use of leaded gasoline was phased-out in Metro Manila in April 2000. This study investigated the distribution of airborne lead in three major thorough fares in Metro Manila. Lead levels in plants and soil surfaces were correlated with both human blood samples and rainwater collected from selected building rooftops in Metro Manila. The range of lead levels in plant species and soil samples were 0.25 to 17.36 mg/kg and 83.74 to 183.51 ug/g, respectively. Lead levels in rainwater and blood samples ranged from 0.95 to 1.29mg/1 and 0.05 to 0.38 ug/g, respectively, showing that lead levels in Manila are beyond allowable limits. There was significant correlation between lead levels of plant species and the different areas of studies, as well as with those of soil and rain water samples. Of the 76 human respondents, with mean age of 39 years old and mean stay in the streets as street workers for 16.5 years, 43.4% of complained of both respiratory and non-respiratory ailments, 30.3% and 22.4% complained chiefly of respiratory and non-respiratory ailments, respectively. The respondents were generally restless and easily distracted Only 25% admitted of committing crime.
Keywords: Solidum, Judilyn N; Heavy metals; Rainwater